RNAi Targets in Agricultural Pest Insects: Advancements, Knowledge Gaps, and IPM - Willow, Jonathan; Taning, Clauvis Nji Tizi; Cook, Samantha M.; Sulg, Silva; Silva, Ana I.; Smagghe, Guy; Veromann, Eve (Frontiers in Agronomy, 2021)
The unprecedented target-specificity of double-stranded RNA (dsRNA), due to its sequence-specific mode of action, puts dsRNA at the forefront of biosafe insecticide technology. Since 2007, sensitive target genes have been identified in numerous crop pest insects, with an end goal of applying RNA interference (RNAi) in pest management. Key RNAi targets identified include genes involved in 1) feeding and digestion, 2) production of dsRNases, 3) resistance to insecticides and plant allelochemicals, 4) reproductive fitness, and 5) transmission of plant viruses. Despite the advances, there remain critical knowledge gaps in each of these areas. Particular emphasis must be placed on ensuring RNAi’s compatibility with integrated pest management (IPM), via further identification of molecular targets that reduce crop damage while sustaining pest (host) populations for highly specialized biocontrol agents, the latter representing a core pillar of IPM.